Influence of Cereal Rye Management on Weed Control in Soybean - Vollmer, Kurt M.; VanGessel, Mark J.; Johnson, Quintin R.; Scott, Barbara A. (Frontiers in Agronomy, 2020)
Cereal rye as a cover crop is often used to improve soil health and as part of integrated weed management programs. Despite this, cereal rye biomass is often not managed for optimal weed suppression. This study evaluated the effects of managing cereal rye as part of an integrated weed management strategy in soybean. Factors consisted of levels of cereal rye management (no cereal rye, no nitrogen, or 20 kg/ha of nitrogen); cereal rye termination timing (20 or 10 d before soybean planting); and residual herbicide treatment applied at cereal rye termination (with or without). Winter annual weed control with cereal rye was generally greater compared to no cereal rye. Winter annual weed control was consistently better when cereal rye was terminated at 20 d before soybean planting compared to 10 d; while summer annual weed control was improved if termination was delayed. Effect of cereal rye management on summer annual weed control varied by weed species. In the absence of residual herbicides, Palmer amaranth control responded to the different levels of cereal rye management. However, morningglory spp. only responded to rye with supplemental N applications. Large crabgrass control was similar for treatments containing cereal rye, regardless of nitrogen input. Our results demonstrate the importance of cover crop management when incorporating cereal rye into an integrated weed management program for soybean.